Associations of levels of peripheral blood leukocyte and subtypes with type 2 diabetes: A longitudinal study of Chinese government employees - Li, Ruimin; Li, Ling; Liu, Bibo; Luo, Dan; Xiao, Shuiyuan (Frontiers in Endocrinology, 2023)
Objectives Available evidence suggests that type 2 diabetes(T2D) may be associated with inflammation and that leukocytes are a topical clinical, biological indicator of inflammation. This study investigates the associations between peripheral blood leukocyte and subtypes levels with T2D. Methods A total of 5,475 individuals were included in the baseline examination from January 2018 to April 2020, with incidence data updated to April 30, 2021, and follow-up to 5,362 individuals. T2D was defined according to the Chinese guidelines for preventing and treating type 2 diabetes. Physiological and biochemical indicators, including leukocyte and subtypes, were obtained from the physical examination results of the tertiary care hospitals relied on at the cohort sites. Covariates such as demographic characteristics and lifestyle were collected by questionnaire. Binary logistic regression and Cox proportional hazard models were used to explore the correlations. Receiver Operating Characteristic (ROC) curves and time-dependent ROC curves were used to estimate the predictive diagnosis of T2D across the subtype of leukocytes. Results The mean follow-up time was 12 months, and the cumulative incidence density of T2D was 4.0/1000 person-years. Cross-sectional results at baseline showed that the levels of peripheral blood leukocyte and its subtypes were higher in the T2D group than in the non-T2D group. Total leukocyte count and subsets levels were grouped by quintile. After adjusting for age, sex, family history of diabetes, lifestyle score, and triglyceride levels, all were compared with the lowest quintile of each group. Logistic regression model results showed that the corrected OR for those with the highest quintile level of leukocyte was 2.01 (95% CI: 1.02-3.98). The longitudinal analysis showed that the adjusted HR was 8.43 (95%CI: 1.06-66.92) for those with the highest quintile level of leukocytes at baseline after controlling for the effects of the above covariates. For those with the highest quintile level of neutrophils at baseline, the adjusted HR was 5.05 (95%CI: 1.01-25.29). The leukocyte and subtypes had predictive values for T2D. Conclusion Patients with T2D have a higher level of peripheral blood leukocyte and subtypes than those without the disease. Elevated leukocyte and neutrophil counts may link to a higher risk of T2D.